Challenges in learning to speak Arabic - Che Haron, Sueraya; Ahmed Mohamed, Ismaiel Hassanein; Mamat, Arifin; Wan Ahmad, Wan Rusli; Rawash, Fouad Mahmoud (Journal of Education and Practice, 2016)
This paper describes a study to investigate the challenges and obstacles to speaking Arabic faced by good and poor Malay speakers of Arabic. The study used individual and focus group interviews with 14 participants to elicit data.The findings revealed 2 types of obstacles, namely, internal and external obstacles. Internal obstacles refer to the limitations that come from the learners’ own selves, knowledge and skills; while external obstacles refer to the constraints that originate from the outside, such as the lack of a supportive environment and sufficient opportunity to speak Arabic. Both good and poor Malay speakers of Arabic felt hampered more by the internal problems than by the external problems. However, it was noted that the good speakers faced more language-related problems than other internal issues, while the poor speakers revealed more internal shortcomings such as lack of confidence and self-esteem.